XRIndex: a brief screening tool for individual differences in security threat detection in x-ray images - Rusconi, Elena; Ferri, Francesca; Viding, Essi; Mitchener-Nissen, Timothy (Frontiers in Human Neuroscience, 2015)
X-ray imaging is a cost-effective technique at security checkpoints that typically require the presence of human operators. We have previously shown that self-reported Attention to Detail can predict threat detection performance with small-vehicle x-ray images (Rusconi et al., 2012). Here we provide evidence for the generality of such a link by having a large sample of naïve participants screen more typical dual-energy x-ray images of hand luggage. The results show that the Attention to Detail score is a linear predictor of threat detection accuracy. We then develop and fine-tune a novel self-report scale for security screening: the XRIndex, which improves on the Attention to Detail scale for predictive power and opacity to interpretation. The XRIndex is not redundant with any of the Big Five personality traits. We validate the XRIndex against security x-ray images with an independent sample of untrained participants and suggest that the XRIndex may be a useful aid for the identification of suitable candidates for professional security training with a focus on x-ray threat detection. Further studies are needed to determine whether this can also apply to trained professionals.